MODERN INSIGHTS OF DNA FUNCTION AND HEREDITY: A REVIEW OF MOLECULAR GENETICS AND CRISPR GENE (Journal of Medical & Health Sciences Review, 2025)
Deoxyribonucleic acid (DNA) serves as the fundamental blueprint for life, governing both the structural development and functional regulation of living organisms. The technology explores the modern understanding of DNA role in heredity and molecular genetics that highlighted key discoveries that have shaped the field. The discovery of intricate molecular mechanisms such as epigenetic modifications, non-coding RNA and the gene environment interactions has evolved beyond Mendelian genetics. The mechanism of genetic inheritance, replication and expression illustrates how traits are passed from one generation to the next generation. This review article highlights how mutation and variations in DNA sequences influence health, evolution and disease susceptibility. A significant focus is placed on revolutionary CRISPR-Cas9 Jain editing technology which has transformed genetic research and holds immense promise for future therapeutic applications. After enabling precise modifications in the genome, CRISPR opens new avenues for the treatment of genetic disorders and advancement in biotechnology. This review emphasizes how the integration of classical molecular genetics with cutting edge gene editing techniques offers a comprehensive understanding of DNA function for addressing agricultural and global health challenges.